Pengaruh Senam Hamil Terhadap Tingkat Kecemasan Ibu Hamil di Rumah Bersalin Bunda Setia - Luh Listya Wahyuni; Sagung Putri Permana Lestari Murdhana Putere; Putu Indah Budiapsari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Anxiety is an uncomfortable psychological condition with a sense of restlessness accompanied by increased physiological changes. The impact of anxiety in pregnancy can affect the growth and development of the baby. Ways that can be implemented to minimize anxiety during pregnancy such as doing light exercise such as exercise for pregnant women. This study aims to find out the effect of giving pregnancy exercises on the level of anxiety of pregnant women at the Mother Setia Maternity Home. The study used analytical techniques with a cross sectional study with a sample size of 50 respondents. Sampling used simple random sampling method. The data collection method used a questionnaire. This study uses univariate and bivariate data analysis with linear regression statistical testing. The results of this study showed that pregnant women who took part in gymnastics had a proportion of mild anxiety 100% and mothers who did not participate in exercise had mild and moderate anxiety levels of 36%. There was a difference in anxiety scores in mothers who took part in gymnastics compared to those who did not (p<0.05). There is an effect of the frequency and gravida of pregnancy exercise on the level of anxiety p<0.05. In conclusion, pregnancy exercise has an effect on the level of anxiety in pregnant women.